Perfusion pattern and time of vascularisation with CEUS increase accuracy in differentiating between benign and malignant tumours in 216 musculoskeletal soft tissue masses. Issue 1 (January 2015) - De Marchi, Armanda; Prever, Elena Brach del; Cavallo, Franco; Pozza, Simona; Linari, Alessandra; Lombardo, Paolo; Comandone, Alessandro; Piana, Raimondo; Faletti, Carlo
Abstract: Introduction: Musculoskeletal Soft Tissue Tumours (STT) are frequent heterogeneous lesions. Guidelines consider a mass larger than 5 cm and deep with respect to the deep fascia potentially malignant. Contrast Enhanced Ultrasound (CEUS) can detect both vascularity and tumour neoangiogenesis. We hypothesised that perfusion patterns and vascularisation time could improve the accuracy of CEUS in discriminating malignant tumours from benign lesions. Materials and methods: 216 STT were studied: 40% benign lesions, 60% malignant tumours, 56% in the lower limbs. Seven CEUS perfusion patterns and three types of vascularisation (arterial-venous uptake, absence of uptake) were applied. Accuracy was evaluated by comparing imaging with the histological diagnosis. Univariate and multivariate analysis, Chi-square test and t -test for independent variables were applied; significance was set at p  < 0.05 level, 95% computed CI. Results: CEUS pattern 6 (inhomogeneous perfusion), arterial uptake and location in the lower limb were associated with high risk of malignancy. CEUS pattern has PPV 77%, rapidity of vascularisation PPV 69%; location in the limbs is the most sensitive indicator, but NPV 52%, PPV 65%. The combination of CEUS-pattern and vascularisation has 74% PPV, 60% NPV, 70% sensitivity. No correlation with size and location in relation to the deep fascia was found. Conclusion: US with CEUS qualitative analysis could be an accurate technique to identify potentially malignant STT, for which second line imaging and biopsy are indicated in Referral Centers. Intense inhomogeneous enhancement with avascular areas and rapid vascularisation time could be useful in discriminating benign from malignant SST, overall when the lower limbs are involved.